Analisis Investasi dan Kelayakan Ekonomi pada Penambangan Sirtu CV Billiant Ningrat di Kecamatan Leles Kabupaten Garut Provinsi Jawa Barat - Nopian Sukmana; Zaenal; Indra Wijaksana (Bandung Conference Series: Mining Engineering, 2023)
Abstract. CV Brilliant Ningrat is a sirtu commodity mining company in Leles District, Garut Regency, West Java Province. The company conducted a study to test the economic feasibility of mining and prospect reserves at the location. In investment analysis, the required data includes initial investment costs and annual mining targets. The Discounted Cash Flow Rate of Return (DCFROR) method is used to analyze economic feasibility by calculating Net Present Value (NPV), Internal Rate Of Return (IRR), and Payback Period (PBP). The results of the analysis show that CV Brilliant Ningrat is economically feasible, because the NPV is Rp83,058,107,084, the IRR is 46.3%, and the PBP is about 2.76 years. A positive NPV value indicates a favorable rate of return on investment, IRR exceeds the minimum expected rate, and PBP is smaller than the mine life, so the investment is considered profitable. Furthermore, a sensitivity analysis was conducted to test the impact of changes in selling prices and production costs on economic viability. The results show that the company risks incurring losses if the selling price falls by 24% and production costs remain fixed. Conversely, if the selling price increases by 76% and production costs remain fixed, the company will also incur a loss. In conclusion, the results of the economic feasibility analysis show that CV Brilliant Ningrat can be considered a profitable investment, but it is necessary to pay attention to resilience to fluctuations in selling prices and production costs. The use of primary and secondary data and analysis using the DCFROR method have provided important information for making investment decisions in the future. Abstrak. CV Brilliant Ningrat adalah perusahaan pertambangan komoditas sirtu di Kecamatan Leles, Kabupaten Garut, Provinsi Jawa Barat. Perusahaan ini melakukan penelitian untuk menguji kelayakan ekonomi tambang dan prospek cadangan di lokasi tersebut. Dalam analisis investasi, data yang diperlukan meliputi biaya investasi awal dan target penambangan tahunan. Metode Discounted Cash Flow Rate of Return (DCFROR) digunakan untuk menganalisis kelayakan ekonomi dengan menghitung Net Present Value (NPV), Internal Rate Of Return (IRR), dan Payback Period (PBP). Hasil analisis menunjukkan bahwa CV Brilliant Ningrat layak secara ekonomi, karena NPV sebesar Rp83.058.107.084, IRR sebesar 46,3%, dan PBP sekitar 2,76 tahun. Nilai NPV yang positif menandakan tingkat pengembalian investasi yang menguntungkan, IRR melebihi tingkat minimum yang diharapkan, dan PBP lebih kecil dari umur tambang, sehingga investasi dianggap menguntungkan. Selanjutnya, dilakukan analisis sensitivitas untuk menguji dampak perubahan harga jual dan biaya produksi terhadap kelayakan ekonomi. Hasilnya menunjukkan bahwa perusahaan berisiko mengalami kerugian jika harga jual turun hingga 24% dan biaya produksi tetap. Sebaliknya, jika harga jual naik hingga 76% dan biaya produksi tetap, perusahaan juga akan mengalami kerugian. Dalam kesimpulannya, hasil analisis kelayakan ekonomi menunjukkan bahwa CV Brilliant Ningrat dapat dianggap sebagai investasi yang menguntungkan, namun perlu memperhatikan ketahanan terhadap fluktuasi harga jual dan biaya produksi. Penggunaan data primer dan sekunder serta analisis menggunakan metode DCFROR telah memberikan informasi penting untuk mengambil keputusan investasi di masa depan.